2019
DOI: 10.1021/acsami.9b19446
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylenimine Hybrid Thin-Shell Hollow Mesoporous Silica Nanoparticles as Vaccine Self-Adjuvants for Cancer Immunotherapy

Abstract: Conventional adjuvants (e.g., aluminum) are insufficient to trigger cell-mediated immunity, which plays a crucial role in triggering specific immunity against cancer. Therefore, developing appropriate adjuvants for cancer vaccines is a central way to stimulate the antitumor immune response. Hollow mesoporous silica nanoparticles (HMSNs) have been proven to stimulate Th1 antitumor immunity in vivo and promote immunological memory in the formulation of novel cancer vaccines. Yet, immune response rates of existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…[ 176 ] Our recent report demonstrated that the hybrid of hollow MSN with positive polymer can remarkably promote their degradable rate. [ 177 ] Furthermore, enhancing the accumulation of inorganic therapeutics in targeted disease‐affected tissues remains a significant challenge and is yet to be solved. For certain diseases, local injection may be considered an alternative drug delivery method for systemic administration.…”
Section: Discussionmentioning
confidence: 99%
“…[ 176 ] Our recent report demonstrated that the hybrid of hollow MSN with positive polymer can remarkably promote their degradable rate. [ 177 ] Furthermore, enhancing the accumulation of inorganic therapeutics in targeted disease‐affected tissues remains a significant challenge and is yet to be solved. For certain diseases, local injection may be considered an alternative drug delivery method for systemic administration.…”
Section: Discussionmentioning
confidence: 99%
“…In acid medium, the amino groups can be protonated and the polymer becomes cationic [8] . Because of the positive surface charge of different materials functionalized with PEI, cell uptake efficiency can be improved [9] . This polymer has been widely applied in regenerative medicine and gene therapy as deliver expression systems [10] .…”
Section: Data Descriptionmentioning
confidence: 99%
“…In addition, MSNs possess adjuvant behaviors due to the properties of morphology, size, and modified groups 140 . Thus far, a myriad of functionalized silica nanoparticles, acting as adjuvants or carriers, have been used for therapeutic cancer vaccines 141,142 . For example, various types of hollow MSNs have been considered as promising vaccine adjuvants to direct humoral and cellular immune responses and subsequently deprive tumor cells during tumor challenge 143 .…”
Section: Inorganic-based Vehiclesmentioning
confidence: 99%